PENENTUAN PENERIMA KIP DENGAN MENGGUNAKAN METODE MOORA PADA SD NEGERI 124395 PEMATANG - Rahmadani Fitri Sinaga; Sundari Retno Andani; Suhada Suhada (STMIK Budi Darma, 2018)
The Smart Indonesia Card (KIP) is an educational cash assistance until graduating from high school with the age of 6-21 years of school age coming from poor families (underprivileged) or who are registered as participants in the Family Hope Program (PKH) or Family Welfare Card (KKS ) The Indonesia Smart Card (KIP) is a refinement part of the Poor Student Assistance Program (BSM) since the end of 2014. The author took a case study on 124395 Public Elementary School. 124395 Public Elementary School is one of the Public Elementary Schools in Pematangsiantar which received the Smart Indonesia Program for students / i poor and have difficult economic constraints. This research is in the background of the problem of KIP provision where the process of delivering assistance sometimes does not meet the target or target. Invalid data causes errors in the distribution of KIP that should be given to recipients who are entitled to receive it. To overcome these problems, a Decision Support System (SPK) is needed which is expected to solve problems in the provision of KIP with the Moora method. The Moora method is a multicriteria decision making method based on each appropriate criterion. The criteria used are: Father's Work, Mother's Work, Father's Income, Mother's Income, Amount of Dependent, Amount of Dependents Still in School, Rapot Value, KKS Holder, Residence, Type of House. SPK KIP is a recommendation to the school, for the next process to be returned to the school.Keywords: Decision Support System, Moora, Indonesia Smart Card (KIP)